Effects of extrusion processing on the nutritional value of dried distillers grains with solubles in diets for nursery pigs - Williams, S.M.; Paulk, C.B.; Issa, S.; Gugle, Terry L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 224 pigs (PIC TR4 × 1050, initially 18.7 lb avg BW) were used in a 21-d experiment to determine the effects of extrusion processing on the nutritional value of dried distillers grains with solubles (DDGS) in diets for nursery pigs. The pigs were weaned at 21 d of age, sorted by sex and ancestry, and blocked by BW. All pigs were fed a common diet for 11 d postweaning and the experimental treatments for the next 21 d. Treatments were a corn-soybean meal-based control and 3 diets formulated with 30% DDGS. The 3 DDGS treatments were either (1) not treated, (2) dry-extruded with the barrel configured for processing cereal grain (to generate less shear and temperature rise), or (3) dry-extruded with the barrel configured for processing soybeans (to generate more shear and temperature rise). Overall, ADG and ADFI both improved (P < 0.02) while F/G became poorer (P < 0.05) for pigs fed the corn-soy control compared to those fed the DDGS treatments. Extruding the DDGS did not affect ADG or F/G (P > 0.11) but did reduce ADFI (P < 0.02). There were no differences in growth performance among pigs fed the DDGS extruded with low vs. high shear (P > 0.20). Pigs fed the corn-soy control diet had greater digestibility of DM, N, and GE (P < 0.02) compared to pigs fed the diets with DDGS. Among the DDGS treatments, extrusion improved digestibility of DM and GE (P < 0.04), but digestibility of N was only improved with high-shear conditions (P < 0.05).
Keywords: Swine; DDGS; Dried distillers grains with solubles; Feed processing; Extrusion